2015
DOI: 10.1177/1087054715611748
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural and Gender Differences in ADHD Among Young Adults

Abstract: Findings extend existing data and suggest a relationship between culture and the development of ADHD, which might be mediated by parenting style.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
3
15
0
Order By: Relevance
“…The total ASRS‐v1.1 Symptom Checklist score estimated in this study suggests that the overall level of ADHD symptoms in the US general adult population (most of whom do not have ADHD) is quite low. Results were consistent with prior research that showed higher ADHD symptom severity among younger and female adults . The normative data generated for the ASRS‐v1.1 Symptom Checklist in this study can be used to assess the deviance of individual scores in clinical settings.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The total ASRS‐v1.1 Symptom Checklist score estimated in this study suggests that the overall level of ADHD symptoms in the US general adult population (most of whom do not have ADHD) is quite low. Results were consistent with prior research that showed higher ADHD symptom severity among younger and female adults . The normative data generated for the ASRS‐v1.1 Symptom Checklist in this study can be used to assess the deviance of individual scores in clinical settings.…”
Section: Discussionsupporting
confidence: 88%
“…Results were consistent with prior research that showed higher ADHD symptom severity among younger and female adults. 15,16 The normative data generated for the ASRS-v1.1 Symptom Checklist in this study can be used to assess the deviance of individual scores in clinical settings. By placing scores in the appropriate demographic context, the results of this study help guide clinicians in understanding a patient's symptom profile and symptom burden, based on his/her ASRS-v1.1 Symptom Checklist score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of ADHD is influenced by cultural factors, meaning that tolerance of hyperactive behavior may differ across cultures. Therefore, ADHD would not be as noticeable by adults in some cultures ( 60 ). Cultural attitudes also influence the type of care patients prefer, accessibility of health care services, and level of trust in health care systems ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dissimilarities may result from differential tolerance of inappropriate behavior across cultures, e.g. cross-cultural differences in authoritative parenting style could be relevant [15]. There are also signifi cant ethnic differences in knowledge and sources of information concerning ADHD and the use of out-of-school behavioral health services [16].…”
Section: Introductionmentioning
confidence: 99%